The concept of right (Haqq) in contemporary Islamic jurisprudence: The dubious form and the vacuous substance - Ansari, Abdul Haseeb; Abu Elgasim , Saad (penseejournal.com, 2014)

(untitled)
Abstract The subject of concern to this paper is the concept of right (haqq) in contemporary Islamic jurisprudence. As to this subject, the paper asserts that it is dubious in form and vacuous in substance. This assertion is not meant to assert that the concept concerned in classical Islamic jurisprudence is not characterized by these characters. That is not because the concept concerned in the jurisprudence concerned, that is classical Islamic jurisprudence, is free from such defects. Instead, that is because the concept concerned in the jurisprudence concerned does not exist at all. What exists, instead, is the concept of hukm shar‘i which is totally different from the concept of right, yet involves a terminology of right in case it is not looked into carefully, one might think, as contemporary Muslim jurists do, that the concept of right exists in Islamic jurisprudence. This paper is of a view that is contrary to that of contemporary jurists and therefore aims at handling the concept disputed over so as to prove its possession of the characters by which it has been described and ultimately deny its existence. To do that, the paper subjects the concept whose existence is denied to a critical analysis after having presented it in a fair descriptive manner showing the way in which right is defined, analyzed and classified. Having done so, the paper arrives at the conclusion that the concept of right in contemporary Islamic jurisprudence is simply an incoherent combination of alien contemporary definitions and indigenous classical regulations. The latter can only be understood within the framework of the classical concept of hukm shar‘i, whereas the former, on the other hand, are either manifestations of the indigenous concept of hukm shar‘i or reflections of alien jurisprudential trends in Western jurisprudence.